New Family of Iterative Methods for Solving Nonlinear Models - Faisal Ali; Waqas Aslam; Kashif Ali; Muhammad Adnan Anwar; Akbar Nadeem (Discrete Dynamics in Nature and Society)
We introduce a new family of iterative methods for solving mathematical models whose governing equations are nonlinear in nature. The new family gives several iterative schemes as special cases. We also give the convergence analysis of our proposed methods. In order to demonstrate the improved performance of newly developed methods, we consider some nonlinear equations along with two complex mathematical models. The graphical analysis for these models is also presented.